2021
DOI: 10.1108/ijaim-09-2020-0144
|View full text |Cite
|
Sign up to set email alerts
|

Dividend policies of travel and leisure firms in the UK

Abstract: Purpose This study aims to examine cash dividend practices of travel and leisure (T&L) companies listed on the London Stock Exchange (LSE). Design/methodology/approach The study uses a panel data set of 524 firm-year observations of 55 unique publicly listed UK T&L companies between 2007 and 2019. First, it uses a modified version of Lintner’s (1956) partial adjustment model for analysis regarding the target payout ratio and dividend smoothing. Second, it performs logit and Tobit models in ascertaini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The return of dividends to shareholders is considered a measure of firm performance (Kilincarslan and Demiralay, 2020; Nguyen et al. , 2020), and one of the leading measures of FP is widely used in the literature (Huang et al.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The return of dividends to shareholders is considered a measure of firm performance (Kilincarslan and Demiralay, 2020; Nguyen et al. , 2020), and one of the leading measures of FP is widely used in the literature (Huang et al.…”
Section: Methodsmentioning
confidence: 99%
“…The study involves quantitative data collection (with 45 questions and data from around 600 social enterprises), qualitative (through interviews with entrepreneurs) and secondary data (to verify the agenda and efforts and compare with other countries). In addition, business experts validate the data to gain critical insight Source: Authors' own work SEJ 20,4 The return of dividends to shareholders is considered a measure of firm performance (Kilincarslan and Demiralay, 2020;Nguyen et al, 2020), and one of the leading measures of FP is widely used in the literature (Huang et al, 2020). Companies use dividends to indicate their excellent financial condition (Chang et al, 2016;Saeed, 2021) (Table 3).…”
Section: Specificationsmentioning
confidence: 99%
“…It is concluded that board size, board independence, and CEO age affect CEO pay. Kilincarslan and Demiralay (2021) analyze travel and leisure companies' dividend policies and financial characteristics. Their findings suggest that companies with high profits are likely to make more dividend payments while highly indebted companies pay fewer dividends.…”
Section: Business Andmentioning
confidence: 99%
“…Large and profitable banks are more likely to pay out dividends (Kabbani et al, 2020). The financial characteristics of a T&L company (ie profitability, debt and size) have a significant effect on the dividend payout decision (Kilincarslan & Demiralay, 2020). The most important determinants of dividends involve income (earnings stability), current and expected future income levels) and past dividend patterns.…”
Section: Introductionmentioning
confidence: 99%